Identification of genetic regulators of longevity in dark-held detached Arabidopsis inflorescences : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Biology, Massey University, Palmerston North, New Zealand. - Jibran, Rubina (Massey University, 2014)
Harvested green plant tissues experience a number of stresses including energy deprivation, water disruption, and changes in hormone levels. These stresses accelerate the senescence of the tissues, which causes their deterioration. A comprehensive understanding of how these stresses cause senescence is essential if this unwanted deterioration is to be minimised. In this thesis, I used detached dark-held immature inflorescences of Arabidopsis thaliana (Arabidopsis) to investigate the regulatory programme responsible for the senescence of harvested energy-deprived tissue. Detached dark-held Arabidopsis inflorescences completely degreened at day 5 when held in the dark at 21°C. The degreening was accelerated by exogenously applying ACC, ethrel, MeJA, and ABA that have previously been shown to accelerate senescence in detached dark-held leaves. Higher MeJA concentrations unexpectedly delayed rather than accelerated degreening of the detached dark-held inflorescences and this was associated with reductions in transcripts for the senescence-associated genes SEN4, ANAC029, NAC3, and SAG12. To identify key genetic regulators of inflorescence senescence an untargeted forward genetics approach was utilized. This involved detaching the immature inflorescences grown from ~20,000 ethyl methane-sulfonate-treated (EMS-treated) Arabidopsis (Landsberg erecta) seeds, holding them in the dark at 21°C and visually identifying those that showed a different timing of degreening to wild type. This approach successfully identified inflorescences that were completely degreened at day 3 of dark incubation (two days earlier than wild type) that were designated accelerated inflorescence senescence (ais) and inflorescences that were more green than wild type at day 5 that were designated delayed inflorescences senescence (dis). A total of 10 ais and 20 dis mutants were identified. Interestingly, most of the dis mutants were specific for inflorescence senescence as they did not show delayed senescence in detached dark-held leaves. By utilizing a traditional map-based cloning approach, five dis mutants were mapped to particular chromosomal regions. dis9 was mapped to the top arm of chromosome 3, dis15 was to the bottom of chromosome 2, and dis1, dis34, and dis58 were mapped to chromosome 4. Whole genome sequencing of dis15 and 58 identified the EMS-induced lesions as G to A transitions in the eukaryotic ASPARTYL PROTEASE (AT2G28030) and NON-CODING RNA (AT4G13495), respectively. Transformation of the AT4G13495 DNA fragment into dis58 reverted the dis58 phenotype to wild-type confirming that the non-coding RNA is involved in regulating inflorescence senescence. In addition to these fertile mutants, a sterile agamouslike mutant that had a sepal-petal-petal phenotype was identified. The mutant showed delayed degreening of detached dark-held inflorescences. This prompted me to investigate the mechanism behind the delayed senescence of the sterile homeotic ag-1 mutant. The sepals of the ag-1 inflorescences were found to have both delayed in planta and detached dark-induced senescence. They were also found to be devoid of JA and like wild-type senesced when treated with MeJA. The delayed in planta sepal senescence appeared to be due to the lack of produced JA as the dde2 mutant (defective in JA biosynthesis and devoid of JA) also showed delayed in planta sepal senescence. However, the dde2 mutant did not show delayed darkinduced senescence suggesting that the delayed dark-induced senescence of ag-1 may be through a mechanism that is unrelated to the JA hormone. Taken together, in addition to identifying common regulators of inflorescence and leaf senescence, this screen has also identified novel regulators specific to inflorescence senescence that traditional screens based on leaf senescence would have missed. This suggests that there are both similarities and differences in the genetic pathways regulating leaf and inflorescence senescence. The identification of a range of mutants, some of which appear to be novel, also indicates that the immature detached Arabidopsis inflorescences are a useful system for studying energydeprivation driven senescence. Understanding the role of the dis58 non coding RNA and the other regulators in the mutant collection offers a new and exciting opportunity for ascertaining the regulatory genetic network initiated in energy-deprived tissues that control the deterioration of harvested produce.
Keywords: Arabidopsis thaliana; Inflorescences; Senescence; Genetic regulation